Pemberdayaan Petani Muhammadiyah untuk Mewujudkan Ketahanan Pangan Banyumas - Sugiyatno Sugiyatno (UM Purwokerto Press, 2023)
Pemberdayaan Petani Muhammadiyah untuk Mewujudkan Ketahanan Pangan Banyumas